Identifikasi VNN dengan Metode PCR pada Ikan Kerapu Cantang (E. fuscoguttatus × E. lanceolatus): Studi Kasus di BPBAP Situbondo - Dina Ahyani; Diamahesa, Wastu Ayu (Journal of Fish Nutrition, 2025)
Viral Nervous Necrosis (VNN), caused by betanodavirus, poses a serious threat to the aquaculture of hybrid grouper (Epinephelus fuscoguttatus × E. lanceolatus), with mortality rates reaching 100% in larval and juvenile stages. This study aimed to develop a VNN detection protocol based on Reverse Transcriptase-Polymerase Chain Reaction (RT-PCR) and nested PCR at the Brackishwater Aquaculture Development Center (BPBAP) in Situbondo, East Java, from February to April 2024. The methodology included necropsy for sampling brain and eye tissues, RNA extraction using a silica-based method, two-step amplification (RT-PCR and nested PCR), and visualization of results through 1.2% agarose gel electrophoresis. The findings revealed that 2 out of 10 hybrid grouper samples (20%) tested positive for VNN, with the detection of a specific 294 bp DNA band. The developed protocol demonstrated high sensitivity (CT values of 18–22 cycles) and optimal specificity, with no false-positive results. Temporal analysis suggested a periodic infection pattern with an 8-week interval. These results confirm the endemicity of VNN at BPBAP Situbondo and underscore the importance of early detection to prevent mass outbreaks. This study recommends implementing the protocol as part of a molecular-based disease surveillance system, along with further development using quantitative PCR (qPCR) for quantitative analysis. The findings are expected to support sustainable VNN control programs in hybrid grouper aquaculture.